Conversation Analysis: Speech Acts in Ibsen’s A Doll’s House - Rahman, Rubina; Gul, Hina (The Journal of Humanities & Social Sciences, 2023)
Conservation analysis has become the focus of investigative interest in recent years among discourse analysts. There is shift towards the investigation of characters in literature through their conversation seen as speech acts. The main goal of this paper is to analyse the use of the locutionary and illocutionary meanings in an extract from Ibsen’s A Doll’s House in order to investigate its impact on the characters’ actions and reactions. An examination has been made of the interplay between the direct and indirect speech acts which steer the plot to its inevitable conclusion. Using these speech acts as tool an analysis has been made of the imperative final conversation between Nora and Helmer, which not only forces Helmer to reconsider his attitude but also changes the course of literature written about women in the 19th century.